2015
DOI: 10.1002/cm.21214
|View full text |Cite
|
Sign up to set email alerts
|

RC/BTB2 is essential for formation of primary cilia in mammalian cells

Abstract: RC/BTB2 is a binding partner of sperm associated antigen 16S (SPAG16S), which is regulator of spermiogenesis in mice, a process during which sperm flagella are formed. The expression of Rc/btb2 is also regulated by multicilin, a protein that controls ciliogenesis. Given that mouse Rc/btb2 mRNA is not only expressed in tissues bearing motile cilia, but also in tissues without motile cilia, we investigated whether RC/BTB2 plays a role in the general process of ciliogenesis by studying two somatic cells lines tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…[66] Perhaps most impressive, another sperm associated protein RC/BTB 2 , that is the interaction partner of SPAG 16S, is essential in the genesis of primary cilia. [67] As we will see shortly, primary cilia are the key to much of the development of complexity.…”
Section: Radiating Functionalitymentioning
confidence: 99%
“…[66] Perhaps most impressive, another sperm associated protein RC/BTB 2 , that is the interaction partner of SPAG 16S, is essential in the genesis of primary cilia. [67] As we will see shortly, primary cilia are the key to much of the development of complexity.…”
Section: Radiating Functionalitymentioning
confidence: 99%
“…Importantly, KIF7 (JBTS12) is implicated in JBTS [198]. In a more direct manner, many proteins have now been identified that localize to the Golgi apparatus and to centrioles and/or primary cilia axonemes: IFT20 [192], RC/BTB2 [199], retinitis pigmentosa protein (RP2) [200], HOOK2 [201], CCDC41 [202], and VPS15 [203]. In light of these studies, the Golgi apparatus appears to be an important extraciliary site for cilia proteins.…”
Section: Extraciliary Sites and Functions Of Ciliary Proteinsmentioning
confidence: 99%
“…To identify whether these genes are affected in female mice, we analyzed the expression of some of these genes in E15.5 embryonic ovaries. We found that the expression of Rcbtb2 (regulator of chromosome condensation [33]) and Rbpms (RNA-binding protein critical repressor of AP-1 signaling [34]) was totally absent in E15.5-treated ovaries (Additional file 1: Fig. S3), which implies that CD targets similar genes in ovaries as well.…”
Section: Resultsmentioning
confidence: 99%
“…We also found a dramatic decrease in the expression of genes such as Rcbtb2 and Rbpms in embryonic ovaries. Rcbtb2 is essential for the formation of primary cilia in mammalian cells [33]. The presence of primary cilia has been documented in granulosa cells, antral follicles and ovarian surface epithelium [54, 55].…”
Section: Discussionmentioning
confidence: 99%